Induction of Labor at 39 Weeks of Gestation Versus Expectant Management for Low-Risk Nulliparous Women: A Cost-effectiveness Analysis. Issue 1 (March 2020) - Hersh, A.R.; Skeith, A.E.; Sargent, J.A.; Caughey, A.B.
Abstract : ( Am J Obstet Gynecol . 2019;220:590.e1–590.e10) Between 1990 and 2010, the rate of induced labor doubled in the United States, largely due to an increase in elective inductions. While elective induction was thought to increase the risk of cesarean delivery, several studies found it did not. The ARRIVE (A Randomized Trial of Induction Versus Expectant Management) Trial found potential benefits in the routine induction of labor at 39 weeks' gestation, including a decrease in the risk of cesarean delivery. Before routine adoption of this practice occurs, several factors, including cost, need to be evaluated. This study aimed to compare induction of labor at 39 weeks gestation for low-risk, nulliparous women in the United States with expectant management in terms of cost-effectiveness.